Hard times - Dickens, Charles, 1812-1870. (United Kingdom : Transatlantic Press, 2012)
Thomas Gradgrind, retired businessman and one of Coketown's most prominent citizens, runs his life and his school along strict utilitarian lines. Fact and reason are his governing principles; imagination and sentiment are to be abhorred and suppressed. Gradgrind raises his children, Tom and Louisa, by the same soulless, barren methods, blighting their young lives. Shorn of emotion because of her upbringing, Louisa yields to a loveless marriage to Gradgrind's boastful, factory-owning friend, Josiah Bounderby, which at least will help advance the career of her beloved brother. Tom, meanwhile, rebels against the strictures of his childhood by falling into dissolute ways, culminating in a plan to rob Bounderby's bank and allow a former employee to be implicated. Dickens sets imagination, compassion and humanity against the sterility of cold hard reason in Hard Times, which he described as a satire on'those who see figures and averages, and nothing else -- the representatives of the wickedest and most enormous vice of this time'. -- from publisher.
Keywords: Dickens, Charles, 1812-1870.; Social problems -- Fiction; England -- Fiction